Serum zinc levels in acute diarrhoea and pneumonia in children aged 6 months to 6 years - Dr. Vinay Kumar Lakkoju; Dr. Nalluru Lakshmi Sravanthi; Dr. Vijayalakshmi Bhimireddy; Dr. Kanta Kumari Pinnamaneni (Pediatric Review: International Journal of Pediatric Research, 2019)
Background & Objectives: To compare serum zinc levels in children suffering from acute gastroenteritis, pneumonia (malnourished and normal) with a control group. To study the effects of zinc in reducing the frequency and duration of diarrhea and pneumonia & its impact on the further recurrence of these infections.Methods: One hundred thirty (130) children in the age group of 6 months to 5 years were included. The Blood samples were drawn for zinc assay from all children at initial presentation and supplement with adjuvant oral zinc for 14 days. The duration of hospital stay and symptom resolution and the effect of supplementation over the next six months on these children was studied.Results: The mean serum zinc levels were significantly lower in children with AGE and Pneumonia as compared to that of the children in the control group which was very highly significant (71.39, 69.45, 81.65 mcg/dl respectively). Also, the malnourished children in both the AGE & LRTI groups had a mean zinc level that was significantly lesser than the adequately nourished children (67.77:73.85 in the AGE group & 57.52: 75.62 in the LRTI group). In the follow-up period for six months, children with undernourishment and those who had low zinc levels at initial presentation had significantly more recurrencesConclusions: Children with AGE and LRTI have a reduced serum zinc level when compared to controls. Zinc supplementation reduces the duration of symptoms in both AGE and LRTI children with low zinc levels and who were undernourished had frequent recurrences.